Karakteristik pada Pasien Ketuban Pecah Dini di RSUP Dr. M. Djamil Padang Tahun 2022 - Rafi Yasnova; Bobby Indra Utama; Roslaili Rasyid (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
Premature rupture of membranes (PROM) is the rupture of the amniotic membranes that happen spontaneously before delivery. This can happen in early (premature) pregnancy or late pregnancy. PROM happens on high-risk pregnancies that are caused by the predisposing factors such as incompetent cervix, abnormal position, excess uterus, CPD and infection. The purpose of this study is to determine the pattern of bacteria that causes premature rupture of membranes in patients at M. Djamil Hospital Padang in 2022. This is a descriptive-based research with the total sampling method using secondary data in the form of a rekam medis. The sample of this study were PROM patients in 2022 that met the inclusion criteria with a total of 16 patients. The results of the study showed that the largest age group was aged ≥ 35 (56.25%) with most patients were high school graduates (56.25%) and employed (62.5%). The most types of bacteria were Gram positive Staphylocoocus aureus with 5 samples (31.25%) and Gram negative bacteria Acinetobacter baumannii with 5 samples (31.25%). The results of the antibiotic sensitivity test showed that gentamicin was the most sensitive antibiotic (100%). Some antibiotics, such as celfazolin, ceftriaxone and cefepime, were resistant antibiotics (100%) while the antibiotics erythromycin and ciprofloxacin were intermediate antibiotics in some of the samples studied, with the respective percentages of antibiotics being 100% and 12.5%. The conclusion of this study is that the most bacteria found in PROM are the Gram-positive bacteria Staphylocoocus aureus and the Gram-negative bacteria, namely Acinetobacter baumannii. The antibiotic susceptibility test showed the most sensitive antibiotics namely gentamicin, the most resistant antibiotics namely celfazolin, ceftriaxone and cefepime and intermediate antibiotics namely erythromycin and ciprofloxacin.